Medical-dental joint counselling for common risk behaviour changes among diabetic patients with periodontitis from public primary care clinics in Kuantan - Osman, Iskandar Firzada; Tin, Myo Han; Md Aris, Mohd Aznan; Ismail, Razida; Yaacob, Munirah; Sidek, Sorayah; Thuraiappah, Mahendran; Abdullah, Fa’iza; Hari, Padmini; Than, Tun Sein; Saub, Roslan (2017)
Growing evidences of bilateral relationship between diabetes (DM) and periodontitis and effectiveness of periodontal therapy on glycaemic control status of diabetic patients with periodontitis (DM-P) encouraged to provide the medical-dental coordinated care. Indentifying and modifying common risk behaviour of DM-P patients prior to and during the coordinated care is critical to achieve treatment-target glycaemic control. Smoking, limited exercise and poor oral hygiene practice (OHP) are the most common risk behaviours for DM-P patients.